2011
DOI: 10.1089/hum.2011.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Adeno-Associated Viral Vector Serotypes for Spinal Cord and Motor Neuron Gene Delivery

Abstract: Gene therapy for motor neuron diseases requires efficient gene delivery to motor neurons (MNs) throughout the spinal cord and brainstem. The present study compared adeno-associated viral (AAV) vector serotypes 1, 6, 8, and 9 for spinal cord delivery in adult mice, by the intraparenchymal or intrathecal route of administration. Whereas intraparenchymal injections resulted in local transduction of the lumbar segment of the spinal cord, intrathecal injections led to a broader distribution, transducing cells along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
142
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(153 citation statements)
references
References 18 publications
8
142
2
1
Order By: Relevance
“…There is considerable variability in the literature regarding the main CNS cell type targeted by AAV9. Several factors have been held accountable for the differences observed, including the route of delivery (73,74), the age at administration (75), the animal species (73,(76)(77)(78), the doses used, the promoter included in the expression cassette (74,79), and even the single-or double-stranded nature of the AAV (80). Alternatively, the quality of vector preparations could play an important role in determining vector tropism (81).…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable variability in the literature regarding the main CNS cell type targeted by AAV9. Several factors have been held accountable for the differences observed, including the route of delivery (73,74), the age at administration (75), the animal species (73,(76)(77)(78), the doses used, the promoter included in the expression cassette (74,79), and even the single-or double-stranded nature of the AAV (80). Alternatively, the quality of vector preparations could play an important role in determining vector tropism (81).…”
Section: Discussionmentioning
confidence: 99%
“…These structural modifications were also accompanied by a diversification of its name and the designations CBA and CB have become common. The development of sc AAV vectors [146] with superior in vivo gene transfer properties [147] but half the genome size (2.3-2.4 kb) has fueled further modifications to the CAG promoter with the original intron being replaced with smaller viral [148], hybrid [149], or synthetic introns (ibid.). As a result of the prolific re-engineering of the basic promoter, the CAG, CBA and CB names have become generic designations to identify a version of these promoters being used to drive transgene expression, but the presence and origin of any introns is seldom described in research articles.…”
Section: New Strategiesmentioning
confidence: 99%
“…AAV9 has the ability to transduce a number of different neural cells types (Foust, Nurre et al 2009). A study by our research group in mice showed that different AAV serotypes had different longitudinal spread within the spinal cord (Snyder, Gray et al 2011) suggesting that similar differences in spread exist within the peripheral nervous system exist.…”
Section: Adeno-associated Vectors (Aav)mentioning
confidence: 99%